Antimicrobial Activity of Some Furans Containing 1,2,4- Triazoles - Zazharskyi, V.; Bigdan, O. A.; Parchenko, V. V.; Parchenko, M. V.; Fotina, T.; Davydenko, P.; Kulishenko, O.; Zazharskaya, N.; Borovik, I.; Бігдан, Олексій Антонович; Парченко, Володимир Володимирович; Парченко, Марина Вікторівна (My University, 2021)
In this study, the antibacterial activity of 11 preparations of drugs was determined by disc diffusion method in agar. Suspensions (0.5×108 CFU) were prepared from the daily cultures of Enterobacteriaceae, Pseudomonadaceae, Staphylococcaceae, Bacillaceae, Listeriaceae, Campylobacteraceae, Nocardiaceae, and Saccharomycetaceae family. The resulting suspensions were cultured on Mueller-Hinton agar, followed by cultivation for 24h. Disks impregnated with the studied preparation were placed on top of the passages. The drug does not dissolve in water, so we used a dilution in 70% ethyl alcohol. The in vitro experiment showed the positive antibacterial effect of 11 preparations on cryogenic strains of Enterobacteriaceae microorganisms: Escherichia coli, Enterococus faecalis, Proteus vulgaris, Serratia marcenses, Klebciella pneumoniae, Salmonella adobraco, Salmonella typhimurium; Pseudomonadaceae families: Pseudomonas aeruginosa, Staphylococcaceae microorganisms: Staphylococcus aureus; Staphylococcus epidermidis; Bacillaceae families: Bacillus subtilis, Listeriaceae: Listeria monocytogenes, Listeria іnnocua, Listeria ivanovi; Campylobacteraceae: Campylobacter jejuni; Nocardiaceae: Rhodococcus equi, and yeasts family Saccharomycetaceae: Candida albicans. The investigated extracts of 5-(furan-2-yl-,5-bromofuran-2-yl)-4H-1,2,4-triazole-3-thiol, 2-(5-(furan-2-yl-, 5-bromofuran-2-yl)-4H-1,2,4-triazole-3-ylthio) acetate, 5-R-2-(furan-2-yl-,5-bromofuran-2-yl) thiazolo [3,2-b] [1,2,4] triazole-4 (5H)-one physicochemical properties can be recommended for additional investigations against polyresistant strains of the mentioned microorganisms. Effective medicines play a key role in public health care and stable veterinary well-being of livestock. This study indicated that the evaluated preparation more intensively affects multiresistant microorganisms than the kanamycin sodium salt.
Keywords: Physicochemical properties; Enterobacteriaceae; Pseudomonadaceae; Staphylococcaceae; Bacillaceae; Listeriaceae